General applied statistics - Zuwaylif, Fadil H. (Reading, Mass. : Addison-Wesley Pub. Co., 1979)
This book was written to serve as a text for a first course in statistics
Includes index.
ijb, 15/01/2019
Loans
Keywords: Mathematical statistics